Noninvasive high-frequency oscillation ventilation as post- extubation respiratory support in neonates: Systematic review and meta-analysis. - Rameshwar Prasad; Bijan Saha; Md Habibullah Sk; Jagdish Prasad Sahoo; Bhupendra Kumar Gupta; Subhash Chandra Shaw (PLoS ONE)
Introduction Noninvasive High-Frequency Oscillatory Ventilation (NHFOV) is increasingly being adopted to reduce the need for invasive ventilation after extubation. Objectives To evaluate the benefits and harms of NHFOV as post-extubation respiratory support in newborns compared to other non-invasive respiratory support modes. Material & methods We included randomized controlled trials comparing NHFOV with other non-invasive modes post-extubation in newborns. Data sources were MEDLINE (via Pubmed), Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, WHO international clinical trials registry platform and Clinical Trial Registry, forward and backward citation search. Methodological quality of studies was assessed by Cochrane's Risk of Bias tool 1.0. Results This systematic review included 21 studies and 3294 participants, the majority of whom were preterm. NHFOV compared to nasal continuous positive airway pressure (NCPAP) reduced reintubation within seven days (RR 0.34, 95% CI 0.22 to 0.53) after extubation. It also reduced extubation failure (RR 0.39, 95% CI 0.30 to 0.51) and reintubation within 72 hrs (RR 0.40, 95% CI 0.31 to 0.53), bronchopulmonary dysplasia (RR 0.59, 95% CI 0.37 to 0.94) and pulmonary air leak (RR 0.46, 95% CI 0.27 to 0.79) compared to NCPAP. The rate of reintubation within seven days (RR 0.62, 95% CI 0.18 to 2.14) was similar whereas extubation failure (RR 0.65, 95% CI 0.50 to 0.83) and reintubation (RR 0.68, 95% CI 0.52 to 0.89) within 72 hrs were lower in NHFOV group compared to nasal intermittent positive pressure ventilation. There was no effect on other outcomes. Overall quality of the evidence was low to very low in both comparisons. Conclusions NHFOV may reduce the rate of reintubation and extubation failure post-extubation without increasing complications. Majority of the trials were exclusively done in preterm neonates. Further research with high methodological quality is warranted.